2020
DOI: 10.1166/jbmb.2020.1970
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Chloroplast Transformation Using CRISPR/Cas9

Abstract: Chloroplasts are organelles that contain genetic materials (DNA) in higher plant cells. The special genetic characteristics of chloroplasts mean that plasmid transformation has important research value, so it has become an important research direction second to nuclear transformation. Although the techniques of chloroplast genome modification have been successfully applied in tobacco and extended to other high plants, there are still many limitations. Exogenous genes are integrated into the chloroplast genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Genes encoding editing tools were delivered into chloroplasts either in the co-transformation mode or as part of an expression cassette along with target genes and a selectable marker in a single vector. The results showed that the efficiency of chloroplast transformation with this supplement increased six-to ten-fold [40].…”
Section: Development Of Crispr/cas9 System To Increase the Efficiency...mentioning
confidence: 91%
See 1 more Smart Citation
“…Genes encoding editing tools were delivered into chloroplasts either in the co-transformation mode or as part of an expression cassette along with target genes and a selectable marker in a single vector. The results showed that the efficiency of chloroplast transformation with this supplement increased six-to ten-fold [40].…”
Section: Development Of Crispr/cas9 System To Increase the Efficiency...mentioning
confidence: 91%
“…These plasmids were shown to be able to autonomously replicate, express and produce Cas9, gRNA and donor DNA within the chloroplasts [39]. By using bioballistics, plasmids that encode editing tools were also successfully delivered into the chloroplasts of tobacco leaves, where they were effectively expressed, increasing the frequency of transgene integration [40].…”
Section: Delivery Of Dna Plasmids Into Chloroplasts Using Bioballisticsmentioning
confidence: 99%
“…An analogous gene construct with the genome-editing system has also been employed to transform tobacco chloroplasts. The authors demonstrated that the targeted DSBs produced by the Cas9/sgRNA complex raise the rate of chloroplast transformation by 6–10-fold [ 170 ].…”
Section: Specific Features Of the Organization Of The Plastid Transcr...mentioning
confidence: 99%